Phytochemistry and biological activities of the genus Ocotea (Lauraceae) : a review on recent research results (2000-2016) - Wan Salleh Wan Mohd Nuzul Hakimi, Ahmad Farediah, (N/A, 2017)
Phytochemistry and biological activities of the genus Ocotea (Lauraceae) : a review on recent research results (2000-2016) by Wan Salleh Wan Mohd Nuzul Hakimi, Ahmad Farediah,